'Am I aware of my roles as a learner?' the relationships of learner autonomy, self-direction and goal commitment to academic achievement among Turkish EFL learners. Issue 1 (2nd January 2023) - Ozer, Omer; Yukselir, Ceyhun
Abstract: This study explores the relationships between learner autonomy (LA), self-directed learning (SDL), goal commitment (GC) and academic achievement in English and also examines the scores which Turkish EFL learners obtained on selected measures according to demographic variables. The participants were 248 English-major Turkish undergraduate students. A mixed-method, embedded design was chosen for this study. The participants completed the Autonomous Learning Scale, the Self-Directed Learning Scale, the Commitment Scale and three open-ended questions regarding their perceptions of LA and SDL in foreign-language learning. The results showed that LA, SDL and GC are all correlated with academic achievement and with each other, with the strongest correlation found between LA and SDL. The findings also revealed statistically significant relationships between Turkish EFL learners' LA scores and all the demographic variables. Furthermore, students' open-ended responses regarding LA and SDL failed to provide particular examples of how learners exercise control over their language learning. Most of the participants in the study were aware of autonomy and self-direction and had an understanding and perception of both LA and SDL. A major implication of this study is that language learners' autonomous learning within but more importantly beyond the classroom should be encouraged.